Impacto del bono de desarrollo humano en la Satisfacción de las necesidades básicas de los beneficiarios, Cantón Catamayo 2022- 2023. - Espinoza Diaz, Dennis Adrian (2024)
The Work of Curricular Integration called "Impact of the HDB Human Development Bonus on meeting the basic needs of beneficiaries, Catamayo Canton 2022-2023", has been implemented to contribute to the solution of the problem, the identification of the distribution of expenditure, the characterization of beneficiary families and the impact on the quality of life. The HDB is a social protection program providing $50 economic support to mitigate the prevalence of poverty in the country. The problem of the beneficiaries arises due to the HDB does not meet their basic needs, therefore, to determine its impact inductive methods were used, emphasizing that the research was not experimental. Surveys and interviews were used through a mixed approach to collect numerical data and perspective-based information and the support of secondary information provided by government institutions, allowing a comprehensive assessment of the experiences of HDB beneficiaries. The analysis of the information involved the codification and tabulation of descriptive statistical data presented through frequency tables and graphs for the fulfillment of the objectives. The study is supported by a sample of 312 beneficiaries in the canton of Catamayo, highlighting significantly the diversity of key sociodemographic variables. In this context, 47% of the participants indicate that food is the most priority need among others, such as Education (31%), Housing (28%) and Health (26%). Significantly, 50% of beneficiaries say that HDB has not contributed to welfare, and they rate its quality 7/10. Finally, the conclusions and recommendations are issued, emphasizing the objectives of the present research.